Semiochemical mediated enhancement of males to complement sterile insect technique in management of the tephritid pest Bactrocera tryoni (Froggatt) - Mohammed Abul Monjur Khan (Nature Portfolio, 2017)
Abstract Queensland fruit fly, Bactrocera tryoni (Froggatt), is the most significant pest of Australia’s $9 billion horticulture industry. The sterile insect technique (SIT) and cue-lure (a synthetic analogue of raspberry ketone (RK))-based male annihilation technique (MAT) are two of the most effective management tools against this pest. However, combining these two approaches is considered incompatible as MAT kills sterile and ‘wild’ males indiscriminately. In the present study we tested the effect of pre-release feeding of B. tryoni on RK on their post-release survival and response to MAT in field cages and in a commercial orchard. In both settings, survival was higher for RK supplemented adults compared to control (i.e. RK denied) adults. A lower number of RK supplemented sterile males were recaptured in MAT baited traps in both the field cages and orchard trials compared to RK denied sterile males. The advantage of this novel “male replacement” approach (relatively selective mortality of wild males at lure-baited traps while simultaneously releasing sterile males) is increasing the ratio of sterile to wild males in the field population, with potential for reducing the number of sterile males to be released.